Innovation strategies and competitiveness of the multisectoral halal industry in the digital era and ASEAN economic integration - Syakirunn’iam, Luqman; Sain, Zohaib Hassan; Lawal, Uthman Shehu (International Journal of Halal Industry, 2025)
Purpose – This study analyzes the multi-sector halal industry’s innovation and competitiveness strategies, including food, cosmetics, pharmaceuticals, tourism, finance, and logistics, in the digital era and the Association of Southeast Asian Nations (ASEAN) economic integration. Methodology – This study uses a qualitative approach with a literature study design. Data were obtained from scientific journals, global halal industry reports, ASEAN economic policies, and previous research relevant to digital innovation and multisector competitiveness. Content analysis is used to identify strategic themes, including innovation patterns, digitalization barriers, and the influence of economic integration on the competitive performance of each sector. Findings – The results show that adopting digital technologies such as e-commerce, digital-based halal certification, and Sharia fintech are the primary drivers of increasing operational efficiency and export market access. ASEAN economic integration expands the halal trade network; however, the gap in technological capabilities between countries and the scale of business remains a challenge. Cross-sector collaboration strategies and regulatory harmonization have emerged as key factors in strengthening the competitive position of the halal industry. Implications – These findings provide policy recommendations for governments, industry players, and investors to accelerate technology adoption, strengthen regional collaboration, and optimize halal export opportunities in global markets. Originality – This study offers a conceptual framework that integrates the theory of competitive advantage and digital innovation in studying the ASEAN halal industry, making a new contribution to the literature on multi-sector innovation strategies in the digital economy era.